2017
DOI: 10.1080/13546805.2017.1285755
|View full text |Cite
|
Sign up to set email alerts
|

Assessing early processing of eye gaze in schizophrenia: measuring the cone of direct gaze and reflexive orienting of attention

Abstract: These results suggest that while patients may suffer deficits associated with interpreting another person's gaze, the earliest processes concerned with detecting averted gaze and reflexively orienting to the gazed-at location are intact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…In other words, the self-referential hyperresponsivity in patients is likely the result of effects manifesting at later stages of deliberative cognitive processing. This aligns with evidence that patients have also demonstrated faster response times when detecting targets that are congruently cued by gaze at longer SOAs-where there is time for deliberative self-referential processes to influence gaze evaluation (Langdon et al, 2017)-and the interpretation that the direct-gaze bias effect observed in patients (when averted gaze is mistakenly judged direct) likely reflects later stages of cognitive processing and selfreferential evaluation, and not fundamental impairments of visual perception (Franck et al,1998;Franck et al, 2002;Seymour et al, 2017).…”
Section: Srtssupporting
confidence: 80%
See 2 more Smart Citations
“…In other words, the self-referential hyperresponsivity in patients is likely the result of effects manifesting at later stages of deliberative cognitive processing. This aligns with evidence that patients have also demonstrated faster response times when detecting targets that are congruently cued by gaze at longer SOAs-where there is time for deliberative self-referential processes to influence gaze evaluation (Langdon et al, 2017)-and the interpretation that the direct-gaze bias effect observed in patients (when averted gaze is mistakenly judged direct) likely reflects later stages of cognitive processing and selfreferential evaluation, and not fundamental impairments of visual perception (Franck et al,1998;Franck et al, 2002;Seymour et al, 2017).…”
Section: Srtssupporting
confidence: 80%
“…These findings suggest that the bias is likely driven by later, conscious processes, rather than the early low-level visual processes that support gaze perception. In line with this interpretation, studies that do not involve a self-referential judgement, and simply instruct participants to report whether the eyes are averted to the left or right, have been unable to reliably identify a direct-gaze bias in patients (Franck et al, 1998;Franck et al, 2002;Seymour, Rhodes, McGuire, Williams, & Langdon, 2017). Summing up these findings, the early perceptual processing of gaze appears to be intact in schizophrenia, while later processes associated with evaluating its social significance may be disrupted (see, e.g., Langdon et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While the CoDG has been shown to be associated with a number of psychopathology traits [6,13,33], there have been inconsistencies in its interpretation. Some have interpreted a wider CoDG as indicative of stronger self-referential tendency [13,31,34], while others have attributed it to poorer precision [35]. Notably, Mareschal et al (2013) showed that while the CoDG width is unaffected by visual noise, the variance in the width is increased.…”
Section: Introductionmentioning
confidence: 99%
“…Although our sample sizes are small, as clinical practice moves toward individualized treatment plans, it is critical that biobehavioral measures are sensitive and reliable at an individual level . Further, small sample sizes have long been used when measuring eye‐movements in schizophrenia patients (for recent work see: Meyhofer et al, ; Seymour et al, ; Thakkar et al, ). We use eye‐movement measures in the present study to examine the effect of a drug treatment and demonstrate robust preliminary findings that significant differences can be observed using the antisaccade task.…”
Section: Discussionmentioning
confidence: 99%